CHARACTERISTICS OF ASSOCIATIVE FIELD FORMATION BASED ON SEMANTIC OPPOSITION - Akhmedova Nargiza Shikhnazarovna (International Journal of Literature and Language Studies, 2026)
This article is dedicated to one of the pressing issues in psycholinguistics: the study of antonyms as associative-verbal structures within the linguistic consciousness. Based on empirical data, the paper analyzes antonymy not merely as a linguistic universal, but as a psychological mechanism inherent in the human psyche. The article provides a scientific rationale for the results of the associative experiment, the nature of linguistic consciousness, and the cueing function of contrasting core concepts in triggering one another.